Republic of Congo : Statistical Annex. (IMF Staff Country Reports; Country Report, 2001)
The report provides the IMF's projections and estimates on the Republic of Congo's basic data and social indicators; gross domestic product at constant 1990 prices and current prices; supply and use of resources at constant 1990 prices and current prices; savings and investment balances; central government employment by ministry; central government revenue, financial operations, revenue and expenditure trends; monetary survey; summary accounts of the central bank and the commercial banks; external trade indices; exchange rate indices; external public debt, during 1995-99; summary of tax system, 2000, and so on.